Control of pancreatic exocrine secretion via muscarinic receptors: which subtype(s) are involved?: a review - Niebergall-Roth, Elke; Singer, Manfred V. (Pancreatology, 2003)
The present report gives an overview of the experimental, pharmacological and molecular investigations that have been undertaken during the past two decades to characterize and identify the muscarinic receptor sub-type(s) involved in the cholinergic control of pancreatic exocrine secretion in humans and different animal species. The results published in the literature clearly indicate that both M1 and M3 receptors contribute to the regulation of pancreatic enzyme secretion, although contradictory conclusions have been drawn from secretory studies using specific M1 and M3 receptor antagonists in vivo and in vitro. Binding studies using specific M1 and M3 receptor antagonists have supported the existence of both M1 and M3 receptors on pancreatic acinar cells, which was confirmed by the demonstration of specific mRNA for both receptor subtypes in rat pancreatic acinar cells. In addition, experimental evidence exists that nonacinar (possibly presynaptic) M1 receptors also contribute to the control of pancreatic enzyme secretion. The role of the different muscarinic receptor subtypes in the control of pancreatic fluid and bicarbonate output, however, still needs to be clarified. Future research should cover the evaluation of the relative contribution of the different receptor subtypes to the regulation of pancreatic exocrine function, the localization of the receptors involved as well as possible species differences.